Study of the effects of neutral gas heating in a radio frequency inductively coupled plasma / Kanesh Kumar Jayapalan - Kanesh Kumar , Jayapalan (2015)
A 13.56 MHz, planar coil, inductively coupled plasma reactor was experimentally and theoretically characterized; with emphasis on the effects of neutral gas heating on the distribution of the H mode magnetic fields of the source coil and the E-H mode transition characteristics of the discharge. The radially resolved electron density, ne, electron temperature, Te and electron energy distribution function (EEDF) were measured using a Langmuir probe at different axial distances above the dielectric plate for 0.03, 0.07 and 0.2 mbar argon pressures. The range of ne and Te obtained were (0.065 ± 0.004)-(4.0 ± 0.6) × 1017 m-3 and (1.38 ± 0.08)-(3.8 ± 0.2) eV assuming Maxwellian distribution. The measured ne distribution at 0.2 mbar suggested significant influence of neutral gas heating. EEDF plots showed that the distributions were Maxwellian-like. The radially resolved absolute axial magnetic field, |Bz|, and absolute radial magnetic fields, |Br|, were measured using electrostatically compensated magnetic probes in the appropriate orientations. The fields were measured at different axial distances above the dielectric plate for the chamber in evacuated condition and for 0.03, 0.07 and 0.2 mbar argon pressures. R.f. power was set at 180 W. Maximum |Bz| and |Br| fields were obtained when the chamber was in evacuated condition with values of (1.507 ± 0.005) × 10-4 T and (7.67 ± 0.01) × 10-5 T, respectively. The peak E-H mode transition current, Itr and peak H-E mode transition current, Imt were measured using a current probe for 0.02-0.2 mbar argon pressures. The minimum value for Itr was (13.5 ± 0.5) A at 0.08 mbar, whereas, the minimum value for Imt was (8.3 ± 0.1) A at 0.3 mbar. As pressure is increased, hysteresis between E-H mode and H-E mode transitions was observed to become more distinct. The line averaged neutral gas temperature, Tn, was measured using a fiber probe with the actinometry optical emission spectroscopy (AOES) technique at 0.03, 0.05, 0.07, 0.1 and 0.2 mbar argon pressure for different axial distances above the dielectric plate. R.f. power was varied from 100 W to 200 W. The range of Tn obtained was (350 ± 30)-(840 ± 30) K. For theoretical characterization, two predictive models were used. The first was an electromagnetic field model that simulates |Bz| and |Br|, using empirically fitted, spatially resolved electron density, ne (r, z) and electron temperature, Te (r, z). Simulations were run for spatially averaged Tn and heuristically fitted, spatially distributed temperature, Tn (r, z). Tn (r, z) gave the closest agreement to the measured magnetic fields. The second model was a power deposition model that simulates Itr and Imt. Simulations were run for Tn = 300 K and at elevated Tn. Calculations better matched the measured values only when neutral gas heating was considered. The effect of hysteresis in mode transition of the discharge was also demonstrated using a fitted 3D power evolution plot. These results indicate that neutral gas heating plays an important role in influencing plasma parameters. Thus, knowledge of the effects of neutral gas heating is essential in providing better understanding of the formation and maintenance of the plasma discharge.